SINGLE NUCLEOTIDE POLYMORPHISMS IN BREAST TUMOR AND EXPRESSION OF ABC-TRANSPORTERS AFTER NEOADJUVANT CHEMOTHERAPY - M. M. Tsyganov; M. K. Ibragimova; E. M. Slonimskaya; N. V. Cherdyntseva; N. V. Litviakov (Сибирский онкологический журнал, 2016)
The mechanism of regulation of ABC transporter gene expression, which is related to individual characteristics of the tumor-bearing organism and its tumor, defined by gene single nucleotide polymorphisms (SNP – Single Nucleotide Polymorphism) has not been extensively studied. We conducted large-scale genome studies of association of SNP with the level of ABC transporter gene expression. The study involved 68 patients with morphologically verified diagnosis of breast cancer treated with neoadjuvant chemotherapy (NAC). Using a quantitative Real-time PCR, the expression of 4 multidrug resistence (MDR) genes (ABCB1, ABCC1, ABCC2, ABCG2) was studied in surgical samples after NAC. Microarray analysis was performed using high density DNA microarrays, which contain more than 750.000 SNPs. Six SNPs significantly associated with postoperative expression levels of multidrug resistance genes, ABCB1, ABCC1, ABCC2, ABCG2, were identified. It was shown that in carriers of a rare genotype, the expression levels of all 4 examined genes in tumors after chemotherapy were either decreased (rs2680835, rs1951366 and rs12018988), or increased (rs4676478, rs6896596, rs1154121) compared to those observed in carriers of frequent and heterozygous genotypes of the SNP. The possible mechanisms of the effect of the identified SNPs and their genes on the expression of ABC transporters were discussed.